Analyzing the performance of DSR protocol on MANET’s network models with various scenarios using ViSim - Rao, N. Thirupathi; Rao, V. Madhusudhan; Bhattacharyya, Debnath; Kim, Tai-Hoon (International Journal of Engineering and Technology, 2018)
The examination of the effect of MANETs in various applications with the usage of various protocols was important to study the performance of these networks. The DSR protocol was one of the most important protocols in MANETs protocols. Hence, this protocol implementation in these sorts of networks with various numbers of nodes was important. A study has been conducted to study the performance of these networks with various numbers of nodes in the network. The behavior of the network was analyzed with various set of nodes. The analyzing of these networks was done with the help of the ViSim simulator. The number of nodes considered for analyzing the performance of the network was three, ten and twenty nodes. An investigation of the conventions has finished the considered parameters that measure the QoS measurement like end-to-end delay, throughput, jitter, outturn and elective system execution measurements. The considered cases were implemented on three different cases and results were discussed in detail. The results show that the performance of the current considered protocol was excellent in the above considered three scenarios.